Nonpharmacological Management of Gastroesophageal Reflux in Preterm Infants - Corvaglia, Luigi (Hindawi Publishing Corporation, 2013)
Gastroesophageal reflux (GOR) is very common among preterm infants, due to several physiological mechanisms. Although GOR should not be usually considered a pathological condition, its therapeutic management still represents a controversial issue among neonatologists; pharmacological overtreatment, often unuseful and potentially harmful, is increasingly widespread. Hence, a stepwise approach, firstly promoting conservative strategies such as body positioning, milk thickening, or changes of feeding modalities, should be considered the most advisable choice in preterm infants with GOR. This review focuses on the conservative management of GOR in the preterm population, aiming to provide a complete overview, based on currently available evidence, on potential benefits and adverse effects of nonpharmacological measures. Nonpharmacological management of GOR might represent a useful tool for neonatologists to reduce the use of antireflux medications, which should be limited to selected cases of symptomatic babies.